Investigating serum biomarkers, disease pathways and vitamin D in association with cardiovascular disease in great apes - Jarvis, Rachel (2025)
Great apes (bonobos, chimpanzees, gorillas and orangutans) in zoological collections play an important role in conservation, and a better understanding of the health challenges they face is crucial. Cardiovascular disease (CVD) is a leading cause of morbidity and mortality, with particular concern arising from a prevalent and poorly understood phenotype: idiopathic myocardial fibrosis (IMF). This thesis investigates diagnostic biomarkers, disease pathways, and vitamin D status as a possible risk factor in CVD, particularly IMF, to address critical knowledge gaps and inform best practice for the management of great apes in human care. The literature review establishes the context for this work by exploring the prevalence and potential aetiopathogeneses of CVD in great apes, highlighting the pressing need for research into IMF. Chapter 1 identifies three potential serum biomarkers of IMF, with one marker in particular showing promise as a novel diagnostic tool, although further validation is required. Chapter 2 assesses the cardiac tissue proteome associated with IMF, showing significant alterations in proteins associated with calcium regulation, mitochondrial and contractile function, and extracellular matrix (ECM) remodelling, revealing key biological pathways involved in IMF progression for the first time. In chapter 3, myocardial gene expression is explored, targeting markers that have been implicated in fibrosis elsewhere. Key pre-analytical and methodological challenges are highlighted, which should be considered in any future work investigating the molecular drivers of IMF. Chapter 4 shifts focus to vitamin D, a potential modifiable risk factor for IMF, revealing widespread low vitamin D status in a large number of great apes in European zoos. UVB exposure, diet, and outdoor access are significant factors influencing vitamin D status in these animals, emphasising the importance of husbandry practices in mitigating potential health risks, though further species-specific investigation is needed. Together, the findings of this thesis advance our understanding of IMF in great apes considerably, and may contribute to the development of evidence-based strategies to improve their health and welfare. Future research should focus on validating novel diagnostic biomarkers and investigating disease pathways in a larger cohort, as well as exploring likely risk factors in conjunction with CVD outcomes more directly, in order to inform interventions to improve health outcomes for these endangered species in human care.